Cómo apresar las competencias del bebé mediante una aplicación de la metodología observacional - M. Teresa Anguera Argilaga (Universidad de La Rioja, 2013)
Among the actual methodologies, the observational one (in natural contexts) is presented as the most usefull because it allows us: to show and capture detectable behaviours, to quantify and to analyse the relationships among them. Specifically, it stands up, not only its fitting to the baby's characteristics, butr the possibilty to study them in their occurrence. The article explains the necessary requisites for: 1) preparing the observation; 2) elaborating the control tools; 3) electing the registrying ways depending on the systematization levels; 4) warranting data's quality, and, 5) the possible observational designs standing out among them the "lag-log" designs as the most complete ones.